2018
DOI: 10.17549/gbfr.2018.23.1.63
|View full text |Cite
|
Sign up to set email alerts
|

Service Marketing Mix Strategy and Service Loyalty towards Hotel’s Success

Abstract: A B S T R A C TThe contribution from service sector is very effective in supporting income growth of a particular country. Hospitality industry has become a mainstay of some developing countries. Hotel services are capable of providing vast employment opportunities, thus demanding the availability of human resources capable of rendering hotel services professionally. The finest services being offered are expected to create service success. The purpose of this research is to identify whether the implemented ser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…If the employee is at the desired level of satisfaction, then the level of commitment to the company will also increase. Ekawati & Yasa [9] suggested that the more efficient and optimally hotels implement the service mix, the more apparent the hotel guest's loyalty to return in the future.…”
Section: Introductionmentioning
confidence: 99%
“…If the employee is at the desired level of satisfaction, then the level of commitment to the company will also increase. Ekawati & Yasa [9] suggested that the more efficient and optimally hotels implement the service mix, the more apparent the hotel guest's loyalty to return in the future.…”
Section: Introductionmentioning
confidence: 99%
“…One of the most noticeable features of services that differentiate them from tangible products is the intangibility (Ekawati, 2018;Kindström 2010;Moeller 2010;Ryu & Han 2010). The intangibility of services makes it rather difficult for consumers to understand the service quality as they do with tangible products (Shin et al, 2017).…”
Section: A Intangibility Of Imported Servicesmentioning
confidence: 99%
“…NPMS, which comprises diverse measures across customers, profits, processes, and innovation, provides an important formal mechanism to collect or produce information that can be used to develop organizational learning (Chenhall, 2005;Hall, 2011;Ekawati and Yasa, 2018). The information provided by NPMS is prerequisite for organizational members' learning about the strategic targets of EC, the behavior patterns for realizing them, and the ways to revise behavior patterns according to the actual outcomes (Henri, 2006).…”
Section: Changes Of Organizational Structure Andmentioning
confidence: 99%